Phytochemical analysis and bioactivity studies of ziziphus mauritiana (twigs and leaves) / Saidatul Aqilah Mohamad Yusof and Rohaiza Saat - Mohamad Yusof, Saidatul Aqilah; Saat, Rohaiza (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Malaysia lack and inadequate research about Ziziphus mauritiana. Two part of Z. mauritiana plant obtained which are leaves and twigs for this study. Z. mauritiana extraction processes conducted using three difference polarity of solvents which are hexane, chloroform and methanol by cool extraction method. The highest yield percentage is chloroform leaves extract which is 3.71%. The phytochemical analysis study revealed that many secondary metabolites presence inside Z. mauritiana such as alkaloid, flavonoid, glycoside, phenol, saponin, steroid, sterol, tannin and terpenoid but for leave part only absence of saponin detected. In thin layer chromatography (TLC) method, the mixture of solvent system used are hexane and chloroform with ratio 3:7 or 1:9 to obtain good separation of compound under short (254 nm) and long (366 nm) wavelength UV lamp. Antibacterial activity examined using disc diffusion method toward Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonella sp. conducted. The highest maximum zone inhibition diameter recorded is hexane leaves crude extract on S. aureus bacteria which is 15 mm. In addition, antioxidant study discovered the highest percentage found on crude extract of methanol.